Realisasi Kegiatan Program Daerah dalam Pengembangan Pembibitan Sapi Potong Guna Mendukung Swasembada Daging Nasional - Bambang Winarso (Jurnal Penelitian Pertanian Terapan, 2014)
Regional autonomy is given broad authority, real and accountable to local governments in proportion. In line with the local government should be able to utilize the potential of area resources optimally. However, under Regulation No 25 ps 2 verse 3, yr 2000 showed that specific authority perbibitan and arrangements regarding disease prevention remains a central government authority in this regard is Breed Livestock Directorate. Do with the efforts to develop livestock breeding cattle in various respo . In an effort to increase the population of cattle beef cattle , a policy that could be done by the East Java Provincial Government "Berlian" program. Meanwhile, Bali local government has declared Simantri Program, Jambi Provincial Government still relies on the center's programs, while in West Java are still doing investigations were the provinces that have the potential technical and non- technical support. This paper is part of the research results about the prospect of Livestock Breeding Beef Cattle Expansion medium scale done in 2012 by the Center for Economic and Social Agriculture . As for the location of the research done in the Province of Bali , East Java , West Java and Jambi Province Keywords: Regional Programme, Beef Cattle Breeding, National Self-Sufficiency